Investigation of antiseptic activity of clay minerals enriched with anthocyanins (LLC "Endo Press", 2020)
Teeth with the elements of destruction in the periapical area are centers of chronic infection, which is used to treat different types of antiseptics. Pelotherapy implemented in gastroenterology, urology, the treatment of infectious diseases. The authors set the task to develop and test in clinical dentistry an alternative method of exposure of anthocyanins-rich clays in the biocoenosis of the root canal system and periapical tissues. The aim of this study was to determine the effect of anthocyanins on the bactericidal activity of clays from Novonelidovskogo and Nechaevsky deposits of the Belgorod region on the biocoenosis of periapical tissues. The results of the first phase of the development of antiseptic on the basis of clay minerals enriched in anthocyanins are presented. With respect to biological material derived from the root canal system in patients suffering from chronic periodontitis, revealed a different bactericidal capacity of the studied clays, depending on their place of production and method of preparation. These results demonstrate the promising perspectives in development of preparations for antiseptic treatment of the root canal system based on natural ion exchangers rich by anthocyanins.